Students' perceptions of academic performance in Distance Education evaluated by Learning Analytics and Ontologies - Costa, Laécio A.; Souza, Marlo; Salvador, Laís N.; Silveira, Aleph C.; Saibel, Celso A. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2021: Anais do XXXII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2021.218423, 2021)
Keeping track of student learning progress in the Distance Education it is a challenge for education specialists because it is always not possible to adopt the same evaluation mechanisms as traditional education due to transactional distance between educators and students. To help educators in the process of evaluating the acquisition of skills and monitoring students' learning experiences, we present the SapeS architecture, which uses Learning Analytics and Ontologies to produce information about student performance. This architecture enables both educators and students to intervene in the teaching process and promotes autonomy to students successfully achieve their planned objectives. This proposal was based on the Design Science Research methodology, which enables the production and evaluation of the proposed solution to better understand its viability in the participant's real context.